Meningkatkan Keterampilan Servis Bawah Bola Voli Siswa Kelas 5B di SDN Bubutan 4 Surabaya melalui Model Pembelajaran PBL - Ariyanto Ariyanto; Advendi Kristiyandaru; Rinda Kuswati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aim of this research is to measure improvement in bottom service skills using a problem-based learning (PBL) model. This research is classroom action research (PTK). The research was conducted at SDN Bubutan 4 Surabaya, and focused on 31 class 5B students. The data collection technique uses a lower service ability test, for indicators of success referring to Djamarah (2006). The percentage indicator for achieving success in this research is the criteria for completing the score for physical education lessons of ≥75 and 80% of the total number of students have exceeded the minimum completeness criteria. The increase in the average student score for cycle 1 activities, had an average score of 68 and a completion percentage of 48.39%, continued in cycle 2 and experienced an increase in the average score of 72 and a student completion percentage of 67.74%. In cycle 3, the average student score increased again by 77 and the percentage of completion was 83.87%.